Hepatitis D virus infection triggers CXCL9-11 upregulation in hepatocytes and liver infiltration of CXCR3+ CD4 T cells - Jan-Hendrik Bockmann; Lena Allweiss; Annika Volmari; David da Fonseca Araújo; Matin Kohsar; Anastasia Hyrina; Janine Kah; Zhijuan Song; Josolyn Chan; Katja Giersch; Tassilo Volz; Marc Lütgehetmann; et al. (JHEP Reports)
Background & Aims: The role of hepatocytes in producing chemokines and triggering liver inflammation and damage in chronic hepatitis D (CHD) is not fully understood. Herein, we investigated the contribution of primary human hepatocytes (PHHs) infected with HDV in triggering inflammation by producing the chemokines CXCL9–11. Methods: We performed quantitative PCR, RNA in situ hybridisation, activation-induced marker (AIM) assays, and FACS analysis to investigate the CXCR3/CXCL9–11 receptor/ligand axis of T cells in peripheral blood and livers from patients with chronic hepatitis B (n = 27 and 18, respectively) and CHD (n = 20 and 18, respectively). Chemokine expression was investigated in cultured HDV-infected PHHs and in livers of HBV- or HBV/HDV-infected humanised mice in the presence or absence of adoptively transferred human immune cells (n = 35 in total). Results: In patient and chimeric mouse livers, higher expression levels of CXCL9–11 were found in an HBV/HDV-coinfected vs. HBV-mono-infected setting. Similarly, high levels of CXCL9–11 were observed in HDV-infected PHHs in vitro. Analysis by RNA in situ hybridisation on patient livers revealed that HDV-infected hepatocytes were a significant contributor to the chemokine expression. The corresponding chemokine receptor CXCR3 was found upregulated specifically on peripheral bulk CD4 T cells of patients with CHD. CXCR3 upregulation was unspecific and was not detected on HDAg- or HBsAg-specific CD4 T cells by activation-induced marker assay. Lastly, adoptive transfer of human T cells in humanised mice led to recruitment of non-HBV/HDV-specific CD4+ T cells only in the setting of HBV/HDV coinfection, but not in HBV-mono-infected mice. Conclusions: HDV infection upregulated the intrahepatic expression of the CXCL9–11/CXCR3 receptor/ligand axis. Higher amounts of HBV/HDV-unspecific CD4 T cells expressing CXCR3 may contribute to the aggravated liver inflammation frequently observed in patients with CHD. Impact and implications: Chronic hepatitis D (CHD) causes the most severe form of viral hepatitis, and treatment options are still limited; therefore, a more precise understanding of CHD immunopathology is needed. In this study, we demonstrated that HDV infection triggers CXCL9–11 expression in hepatocytes and liver infiltration of CXCR3-expressing CD4 T cells in preclinical models as well as patient biopsies. Because recruitment of Th1-polarised CD4 T cells to the liver has been also described for other severe liver diseases, such as autoimmune hepatitis, it may represent an important mechanism of aggravating liver diseases. The data of this study set hereby the basis for future studies analysing phenotype and function of intrahepatic T cells in CHD.